Area formula for centered Hausdorff measures in metric spaces. (October 2015) - Franchi, Bruno; Serapioni, Raul Paolo; Serra Cassano, Francesco
Abstract: Motivated by an example in Magnani (in press), we study, inside a separable metric space ( X, d ), the relations between centered and non centered m -dimensional densities of a Radon measure μ in X and their relations with spherical and centered spherical m -dimensional Hausdorff measures. Eventually we give an application to finite perimeter sets in Carnot groups.